2001
DOI: 10.1177/089686080102100213
|View full text |Cite
|
Sign up to set email alerts
|

Qt Dispersion and Signal-Averaged Electrocardiogram in Hemodialysis and Capd Patients

Abstract: Objective The aim of this study was to compare QT dispersion (QTd) and signal-averaged electrocardiogram (SA-ECG) parameters that may predict risk of malignant arrhythmias in patients on hemodialysis (HD), on continuous ambulatory peritoneal dialysis (CAPD), and in controls. Setting Controlled cross-sectional study in a tertiary- care setting. Patients 28 HD (M/F 18/10; mean age 32 ± 9 years), 29 CAPD (M/F 17/12; mean age 34 ± 10 years), and 29 healthy controls (M/F 17/12; mean age 32 ± 8 years) were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…The prolongation of QT dispersion in dialysis patients did not relate to gender, age, duration of dialysis, pH values, Kt/V or the serum levels of electrolytes. 10,25,26 A correlation with the left ventricular mass index was observed in HD patients, 5 but not in PD patients. 5,10 A prolonged QT dispersion is usually associated with an increased sympathetic drive, 18 but the association was not confirmed in ESRD patients.…”
Section: Other Factors Relating To the Prolongation Of Qt Dispersion mentioning
confidence: 92%
See 3 more Smart Citations
“…The prolongation of QT dispersion in dialysis patients did not relate to gender, age, duration of dialysis, pH values, Kt/V or the serum levels of electrolytes. 10,25,26 A correlation with the left ventricular mass index was observed in HD patients, 5 but not in PD patients. 5,10 A prolonged QT dispersion is usually associated with an increased sympathetic drive, 18 but the association was not confirmed in ESRD patients.…”
Section: Other Factors Relating To the Prolongation Of Qt Dispersion mentioning
confidence: 92%
“…Patients with chronic renal failure had a greater QTc interval and QTc dispersion compared with the control subjects. 5,23 High rates of QT dispersion have been observed in patients who receive continuous ambulatory peritoneal dialysis (CAPD). 10,23 It has been reported that a single session of HD might further increase QTc dispersion in both adults and children with chronic HD.…”
Section: Greater Qt Dispersion In Dialysis Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Many studies have reported that QT dispersion is prolonged in adults with chronic renal failure, particularly in the period immediately after the end of haemodialysis. [16][17][18][19][20][21][22][23][24] Very recently, corrected QT (QTc) dispersion has been demonstrated to be a useful marker for identifying dialysis patients at an increased risk for overall and cardiovascular mortality. 19 However, there are limited data regarding changes in QT interval and QT dispersion in the children receiving haemodialysis.…”
Section: Introductionmentioning
confidence: 99%